Competências para internacionalização em empresas agroindustriais: estudos de caso em frigoríficos brasileiros - Santos, Alexandre Borges (2018)
The literature on corporate internationalization has a solid theoretical background, the result of long years of intense debate based on studies mostly carried out with multinational enterprises from developed countries. However, there are several conditioning factors in this type of analysis that need to be better understood, especially those related to characteristics of specific sectors of the economy. This is the case of agribusiness. Since some companies have achieved global leadership, the analysis of the internationalization process of some relatively well-positioned Brazilian agrifood multinationals in the global economy could help to extend the knowledge in the field of international management by incorporating specific elements of agro-industry. The main objective of this work, therefore, is to identify and evaluate the core competences for the internationalization of Brazilian slaughterhouses. Concomitantly, an analytical framework based on the principles of the behavioral model of internationalization, the resource-based view and the agrifood supply chains was proposed and empirically tested. To achieve these objectives, exploratory case studies were conducted with four Brazilian slaughterhouses with international presence. Directors and managers with extensive knowledge of the international operations and that were involved at some point and in some way in the internationalization decisions of the companies were interviewed. In general, empirical evidence suggests the existence of two levels of competences for internationalization: generic and core competences. The generic competences are those related to the specificities of the agrifood chains in general, therefore, common to all internationalized slaughterhouses. The core competences, on the other hand, are rare and begin to be developed soon after the birth of the multinational enterprise. The barriers, the motivations and the entry modes common to the cases were identified and discussed. All these elements were incorporated into the proposed framework. The results of this study reinforce the importance of the study of sectoral elements (meso-level) for the identification of competences (micro-level) for internationalization of agribusiness enterprises.